2022
DOI: 10.1007/s10669-022-09870-2
|View full text |Cite
|
Sign up to set email alerts
|

(Re)Conceptualizing decision-making tools in a risk governance framework for emerging technologies—the case of nanomaterials

Abstract: The utility of decision-making tools for the risk governance of nanotechnology is at the core of this paper. Those working in nanotechnology risk management have been prolific in creating such tools, many derived from European FP7 and H2020-funded projects. What is less clear is how such tools might assist the overarching ambition of creating a fair system of risk governance. In this paper, we reflect upon the role that tools might and should play in any system of risk governance. With many tools designed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Such activities are fundamental in clarifying the utility of decision-making tools for the risk governance of nanotechnology might assist the overarching ambition of creating a fair system of risk governance. 26…”
Section: Business Modelsmentioning
confidence: 99%
“…Such activities are fundamental in clarifying the utility of decision-making tools for the risk governance of nanotechnology might assist the overarching ambition of creating a fair system of risk governance. 26…”
Section: Business Modelsmentioning
confidence: 99%
“…While integration is essential for risk management and frequently advocated, balanced integration often fails (e.g., Miller and Wickson, 2015;Patenaude et al, 2015). Indeed, an earlier review of existing governance frameworks suggested that despite a long-standing interest in integrating stakeholder concerns in risk governance, agreement on how to implement such accommodating mechanisms has thus far proved elusive (Mullins et al, 2022). This is in part due to the incommensurability of 'hard' scientific risk assessment data with 'soft' qualitative data from concern assessment (Mullins et al, 2022).…”
Section: Qualitative and Qualitative Datamentioning
confidence: 99%
“…It comprises six subsequent interlinked elements. It includes risk management models, tools and approaches relevant to nanomaterials, as well as nano-oriented LCA and grouping, and takes into account socio-economic aspects and risk-benefit assessment (Franken et al, 2019;Sørensen et al, 2019;Isigonis et al, 2020;Mullins et al, 2022). (see Figure 1):…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials, with their dimensions on the order of 10 −9 meters, are renowned for their high chemical reactivity and the quantum effects that they display, traits that make them particularly suitable for commercial product development. Though these materials can be found in nature, they are often synthesized through various techniques, including decomposition and combustion methods [1][2][3].…”
Section: Introductionmentioning
confidence: 99%